Екологічна ситуація в Україні - Москалюк, Інна Вікторівна; Сакун, Микола Миколаєвич; Нагорнюк, Володимир Федорович (НТУ "ХПІ", 2017)
Україна – одна із найурбанізованіших країн – у містах мешкає майже 70% населення. Висока концентрація техногенних об'єктів сприяє забрудненню довкілля, знижує комфортність життя. Основними джерелами забруднення атмосфери міста є транспорт, енергетичні системи та промисловість. Розвиток промисловості супроводжується професійним травматизмом працівників. Реальні виробничі умови є причиною виникнення шкідливих та небезпечних виробничих факторів, які призводять до матеріальних і моральних втрат та негативно позначаються на рівні життя населення.

Ukraine – one of industrial countries – a 70 % population lives in cities almost. The high concentration of technogenic objects assists contamination of environment, reduces the comfort of life. The basic sources of contamination of atmosphere of city are a transport, power systems and industry. Noise, oscillation and electromagnetic contamination of cities is formed as a result. Development of industry and expansion of production are in the whole world accompanied by the professional traumatism of workers as a result of violation of accident, neglect of facilities of individual defence, unperfection of technologies, machines, mechanisms and instruments prevention, and also in connection with unsatisfactory organization of productive process. Before the origin of accidents and professional diseases absence and failure to observe of the physiology modes of labour lead also. The real productive terms are reason origins of harmful and dangerous productive factors, the consequence of that is professional diseases, accidents and traumatism, that result in material and moral losses and negatively designated at the level of life of population. A problem of forming of ecological consciousness for Ukrainian society is urgent, and in the nearest decades she must become the major factor of his development. People must deeper go deep and educe main reasons that resulted in the threatening state of environment of Ukraine, and educe consequences that are a result mainly careless relation of humanity, namely in our state, to the environment.
Ecological situation in Ukraine
Keywords: аварії; катастрофи; екологічна ситуація; надзвичайні ситуації; техногенне середовище; accidents; catastrophes; ecological situation; statistics; emergencies; technogenic environment